Comparison of Outcome of Conventional Miniplates Versus 3-D Miniplates for Reduction of Mandibular Fractures - Tazeem Ul Hassnain, Umer Hussain, Wajiha Abbas, Muhammad Athar Khan, Muhammad Azeem Khan, Muhammad Junaid Hashmi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mandibular fracture, also known as fracture of the jaw, is a sudden discontinuity through the mandibular bone. In the treatment of un-favorable mandibular angle fractures, 3D plating system was analogous to double miniplates Osteosynthesis. Over the last century, the indicators for closed vs. open reduction have shifted considerably. Objective: To compare the outcome of conventional miniplates versus 3-D miniplates for reduction of mandibular fractures Material & Methods Study Design: It was randomized control trial Setting: Department of Oral & Maxillofacial Surgery, Mayo Hospital, Lahore Duration: 6 months i.e. from 24-04-2017 to 24-10-2017 Data collection: 70 mandibular fracture patients were enrolled. The patients were split into two groups. Group A is treated with 3D plates technique and group B treated with conventional mini plate technique. After surgery patients were evaluated for plate failure or and at 1 month for occlusal discrepancy. All the data was entered and put in SPSS version 21. Results: In this study the mean age of the group A patients was 29.29±1.802 years whereas the mean value of age in group B patients was 35.69±11.65 years, male/female ratio of the patients was 1.05:1. Plate was successfully inserted in 100% patients by 3D mini-plate technique. The occlusal discrepancy was noted in 8(11.43%) patients (p-value=0.005). Conclusion: 3-D mini-plates for reduction of mandibular fractures is significantly more efficacious than to conventional mini-plates method